Tailoring the global network for real burden sharing at sea - Lawrence, Mark W. (CSIS report, 2015)
"The U.S. Navy's requirement to implement a longstanding rhetorical commitment to partnerships at sea was articulated in the 2012 Defense Strategic Guidance, confirmed in the 2014 Quadrennial Defense Review, and was most recently reiterated in the new Cooperative Strategy for 21st Century Seapower: Forward, Engaged, Ready. As a means to offset the risks inherent in divesting some maritime presence requirements and being challenged to ensure operational access, however, the Navy's current efforts fall short of the requirement. As an unclassified, service-specific look at an increasingly important defense policy area, Tailoring the Global Network for Real Burden-Sharing at Sea looks at what the Navy can do from the bottom up to provide for deeper, more structured partnerships as part of a federated approach to defense"--Publisher's web site